Assessing the prevalence of mycoplasma contamination in cell culture via a survey of NCBI's RNA-seq archive - Olarerin-George, Anthony O.; Hogenesch, John B. (Nucleic acids research, 2015)
Mycoplasmas are notorious contaminants of cell culture and can have profound effects on host cell biology by depriving cells of nutrients and inducing global changes in gene expression. Over the last two decades, sentinel testing has revealed wide-ranging contamination rates in mammalian culture. To obtain an unbiased assessment from hundreds of labs, we analyzed sequence data from 9395 rodent and primate samples from 884 series in the NCBI Sequence Read Archive. We found 11% of these series were contaminated (defined as ≥100 reads/million mapping to mycoplasma in one or more samples). Ninety percent of mycoplasma-mapped reads aligned to ribosomal RNA. This was unexpected given 37% of contaminated series used poly(A)-selection for mRNA enrichment. Lastly, we examined the relationship between mycoplasma contamination and host gene expression in a single cell RNA-seq dataset and found 61 host genes (P < 0.001) were significantly associated with mycoplasma-mapped read counts. In all, this study suggests mycoplasma contamination is still prevalent today and poses substantial risk to research quality.